Advances in the treatment of Hodgkin lymphoma: Current and future approaches - Ullah, Fauzia; Dima, Danai; Omar, Najiullah; Ogbue, Olisaemeka; Ahmed, Sairah (Frontiers in Oncology, 2023)
Hodgkin lymphoma (HL) is a rare type of lymphoma with unique histologic, immunophenotypic, and clinical features. It represents approximately one-tenth of lymphomas diagnosed in the United States and consists of two subtypes: classical Hodgkin’s lymphoma (cHL), which accounts for majority of HL cases, and nodular lymphocyte predominant Hodgkin lymphoma represent approximately 5% of Hodgkin lymphoma cases. From this point, we will be focusing on cHL in this review. In general, it is considered a highly curable disease with first-line chemotherapy with or without the addition of radiotherapy. However, there are patients with disease that relapses or fails to respond to frontline regimens and the standard treatment modality for chemo sensitive cHL is high dose chemotherapy followed by autologous hematopoietic stem cell transplant (AHSCT). In recent years, targeted immunotherapy has revolutionized the treatment of cHL while many novel agents are being explored in addition to chimeric antigen receptor (CAR) T-cell therapy which is also being investigated in clinical trials as a potential treatment option.